Spatial-network, general-equilibrium model with a stylized application - Lofgren, Hans; Robinson, Sherman (Elsevier, 2002)
Spatial aspects of economic policy are often important. However, multi-region computable general equilibrium (CGE) models have rarely explicitly treated geographical space. This paper develops a spatial-network, mixed-complementarity CGE model, incorporating formulations from partial-equilibrium programming models. We implement the model with a prototype data set for a stylized, poor, developing country with rural regions linked to an urban region that is linked to international markets. We demonstrate that the model provides a good framework for analyzing the impact of higher world prices and reduced domestic transportation costs and that the explicit incorporation of space has a strong impact on simulation results.